Synthesis of silica aerosol gels via controlled detonation - Dhaubhadel, R.; Rieker, T. P.; Chakrabarti, A.; Sorensen, Christopher M. (My University, 2011)
Silica (SiO[subscript]2) aerosol gels were formed via Brownian aggregation of silica nanoparticles in a closed reaction chamber. A sudden and quick detonation reaction of pyrophoric silane (SiH[subscript]4) with either oxygen or nitrous oxide created silica nanoparticles with diameters ranging from ~ 22 to 90 nm in the presence of an inert background gas with a volume fraction of ca. 10[superscript]-4, conditions necessary for gelation. The background gas was necessary for quick thermal quenching of freshly formed silica molecules and molten nanoparticles and some control of the particle size could be achieved by variation of the gas. The silica aerosol gels were found to have very low densities in the range 4 to 15 mg/cm[superscript]3 and high specific surface areas of 300 to 500 m[superscript]2/g. Wide angle X-ray diffraction showed that the nanoparticles were amorphous silica. Neutron scattering showed that they were arranged in networks with a fractal dimension of 1.75 between 10 to 1000nm length scales.
Keywords: Silica aerosol gels; Nanoparticles; Fractal aggregates; Synthesis